Swarnamakshika- A Review Through Classics. - Abhilasha, Thakur; Sudarshan, Thakur K; Chaudhary, Vijay (International Research Journal of Ayurveda & Yoga, 2023)
Rasa Shastra is a branch of science which tend to facilitate human beings with the aid of systematic use of metals, minerals and herbal drugs to achieve longevity. Swarnamakshika is one of the important minerals which is used solely or as an ingredient in many formulations for curing many diseases such as Pandu (Anaemia), Prameha (Diabetes), Anidra (Insomnia) etc. In classics it has been described as Saklamyaghana (cure all the diseases) In Ayurveda, the utilization of metals and minerals comes under Rasachikitsa. These minerals can be used for internal administration only after their fundamental processing’s. These processing techniques are Shodhana (purification), Marana (incineration) and Satvapatna (extraction of core element). Swarnamakshika is a mineral which contains copper and iron. In mineralogy, it is called as Chalcopyrite. Swarnamakshika has been described in various classical texts. This current review paper highlights the description of Swarnamakshika available in various Rasa Shastra and other classical texts.